2005
DOI: 10.1016/j.annemergmed.2005.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physicians' Fear of Malpractice in Evaluating Patients With Possible Acute Cardiac Ischemia

Abstract: Malpractice fear accounts for significant variability in ED decisionmaking and is associated with increased hospitalization of low-risk patients and increased use of diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(151 citation statements)
references
References 30 publications
4
141
5
1
Order By: Relevance
“…38 Fear of malpractice was measured using two of six questions from a previously published measure (Q1:I feel pressured in my day- Table 1a to-day practice by the threat of malpractice litigation, Q2:I order some tests or consultations to reduce by risk of being sued; 5 point-strongly disagree to strongly agree;Cronbach's alpha 0.76, in our study). 39,40 Physicians reported practice characteristics, including the average number of outpatients seen weekly and practice type (i.e., solo, single specialty group, multispecialty group). Practice census division and rurality were determined from the mailing ZIP codes, using Rural Urban Commuting Area (RUCA) codes to designate level of rurality.…”
Section: Independent Variablesmentioning
confidence: 99%
“…38 Fear of malpractice was measured using two of six questions from a previously published measure (Q1:I feel pressured in my day- Table 1a to-day practice by the threat of malpractice litigation, Q2:I order some tests or consultations to reduce by risk of being sued; 5 point-strongly disagree to strongly agree;Cronbach's alpha 0.76, in our study). 39,40 Physicians reported practice characteristics, including the average number of outpatients seen weekly and practice type (i.e., solo, single specialty group, multispecialty group). Practice census division and rurality were determined from the mailing ZIP codes, using Rural Urban Commuting Area (RUCA) codes to designate level of rurality.…”
Section: Independent Variablesmentioning
confidence: 99%
“…27 Other studies have investigated characteristics of physicians that may affect the decision-making process, such as their attitudes toward risk, fear of malpractice, and bias. [28][29][30] in a prospectively identified cohort of patients with chest pain meeting enrolment criteria for a study of coronary computed tomographic angiography (CCTA) and admitted for a ''rule out ACS'' protocol.…”
Section: Ré Sumémentioning
confidence: 99%
“…Several studies have shown that physicians often practice what is termed as defensive medicine, i.e. order tests or procedures, primarily due to fear of litigation (Kessler & McClellan 1996, Studderrt, et al 2005Katz et al 2005).…”
Section: The Formation Of Doctorsmentioning
confidence: 99%